Pendekatan Sejarah Dalam Penelitian Pendidikan - Maulida Rizqi Solikhah (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
Abstract: The basis for discussing or solving problems related to religion requires a way to see and explain Islam from various sides. This method is an approach that can study Islam more objectively. The use of history as an approach can target various past events based on actual facts and data. The historical approach can make improvements to a probem rationally and structured, by collecting, assessing, examining, and associating forms of truth in order to solve religious cases with strong information and conclusions. So that the harmony and gaps that exist in the real world can be seen. The methods that can be used in the historical approach are related to one another. The methods include the heuristic method, the critical method, the interpretation method, and the historiography method.   Keywords: Approach, History, Religious Research